Contract of sale of goods - Eishan Jan, Mohammad Naqib; Lin, Low Yok (CLJ Malaysia Sdn. Bhd, 2024)
A contract of sale of goods is a contract by which the seller transfers or agrees to transfer the ownership of the goods to the buyer at a price. In Malaysia, the Sale of Goods Act 19571 (SOGA) primarily governs contracts for the sale of goods and, to some extent, works in conjunction with the Contracts Act 1950 and the Consumer Protection Act 1999. As a fundamental law, the SOGA serves to redress consumers when their purchases go wrong. It is crucial for every person who sells goods or services to understand the consequences of this law and their duties under it. The SOGA stipulates that all descriptions, whether oral, written, implied, or represented by sample, must be accurate and not misleading. Misrepresentation of goods allows the buyer to claim against the seller for breach of contract, rendering the seller in violation of the law. The contract for the sale of goods is one of the most important contracts a business owner can enter into. You might be drafting a contract to provide goods and services to your customers, or perhaps you are considering a new bulk purchase deal. Either way, determining the appropriate language to include or exclude can save you significant time and money. Beyond the definition of a contract of sale, this chapter provides an assessment of key aspects of a contract for the sale of goods, including contract formation, contract capacity, price, transfer of ownership, transfer of title, and implied terms and warranties.